Customer satisfaction at a cell phone repair shop in Oeiras, Piauí - Sousa, Warlly Vinícius Pereira Ribeiro de; Silva, Marina Bezerra da; Oliveira, Felipe Moura (Brazilian Journal of Production Engineering, 2025)
Meeting customer expectations is essential for the survival of companies in the market, especially in the fast-growing mobile phone repair sector. This study aimed to analyze customer satisfaction levels at a technical assistance store in Oeiras-PI, a city with around 37,000 inhabitants and a high number of smartphones per capita. The SERVQUAL methodology was applied through a questionnaire, to enterprise consumers, that evaluates the gap between expectations and actual service perceptions, considering dimensions such as tangibility, reliability, and empathy. The results revealed dissatisfaction in aspects related to accessibility, service execution time, and the organization of the physical environment. These factors negatively affect the customer experience, especially for elderly individuals and people with disabilities. As a conclusion, corrective measures are recommended, including improvements to physical infrastructure, greater accessibility, and investments in equipment to optimize services. The study reinforces the usefulness of the SERVQUAL scale as a diagnostic tool for entrepreneurs in the sector, contributing to service quality improvement and customer loyalty.